MECHANISMS FOR ASSESSING AND INCREASING FINANCIAL EFFICIENCY IN THE PRIVATIZATION OF STATE-OWNED ENTERPRISES - Asomidinova Moxigulbonu Oybek kizi (World Scientific Research Journal, 2025)
Annotation: This article explores mechanisms for assessing and enhancing financial efficiency during the privatization of state-owned enterprises (SOEs). The process of transferring state assets into private ownership is not only an economic reform but also a crucial step toward increasing competitiveness, productivity, and fiscal sustainability. The study focuses on evaluating methods of financial performance assessment, identifying efficiency gaps, and developing mechanisms to ensure value maximization in privatization. The findings reveal that successful privatization requires a combination of transparent valuation methods, effective governance reforms, strategic investor participation, and performance monitoring tools.